Sosialisasi Program Pendampingan SMART Silase Management (Teknologi Pengolahan Hijauan Pakan) di Peternakan D’Mumtaz Karanganyar - Ina Nurtanti; Desna Ayu Wijayanti; Dzikrina Aqsha Mahardika (Yayasan Literasi Sains Indonesia, 2025)
Forage feed is the main component in ruminant livestock farming. The main problem faced by smallholder farmers is the fluctuating availability of forage, especially during the long dry season. Silage technology becomes a strategic alternative in providing durable, high-quality, nutritious, and economical feed. This community service program was carried out at D’Mumtaz Farm, Karanganyar, with the aim of enhancing farmers’ capacity in forage processing through the innovative SMART Silage Management approach. The methods included socialization, participatory training, technical demonstrations, and continuous mentoring. The results showed a significant improvement in farmers’ understanding and skills in raw material selection, anaerobic fermentation techniques, and proper silage storage management. Evaluation revealed that 85% of participants were able to produce quality silage according to indicators of aroma, texture, color, and essential nutrient content. The SMART approach has proven effective in helping farmers plan feed production more efficiently, measurably, systematically, and with a focus on business sustainability through digitalization. This program is expected to become an outstanding replication model in empowering farmers based on innovative and competitive forage feed technology.